2006
DOI: 10.1002/jcp.20601
|View full text |Cite
|
Sign up to set email alerts
|

TP53 and p16INK4A, but not H‐KI‐Ras, are involved in tumorigenesis and progression of pleomorphic adenomas

Abstract: The putative role of TP53 and p16 INK4A tumor suppressor genes and Ras oncogenes in the development and progression of salivary gland neoplasias was studied in 28 cases of pleomorphic adenomas (PA), 4 cases of cystic adenocarcinomas, and 1 case of carcinoma ex-PA. Genetic and epigenetic alterations in the above genes were analyzed by Polymerase Chain Reaction/Single Strand Conformational Polymorphism (PCR/SSCP) and sequencing and by Methylation Specific-PCR (MS-PCR). Mutations in TP53 were found in 14% (4/28) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
2
22
1
Order By: Relevance
“…We suggest that this increased risk is due to coamplification of other cancer-associated genes in 12q, in particular MDM2 which was amplified in all but one of the tumors with 12q amplicons. The fact that amplification/overexpression of MDM2 is an alternative mechanism for inactivation of TP53 together with the observation that TP53 is frequently mutated in Ca-ex-PA and almost never in benign PA (Nordkvist et al, 2000;Augello et al, 2006) provide additional support for a role of MDM2 in malignant transformation of PA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that this increased risk is due to coamplification of other cancer-associated genes in 12q, in particular MDM2 which was amplified in all but one of the tumors with 12q amplicons. The fact that amplification/overexpression of MDM2 is an alternative mechanism for inactivation of TP53 together with the observation that TP53 is frequently mutated in Ca-ex-PA and almost never in benign PA (Nordkvist et al, 2000;Augello et al, 2006) provide additional support for a role of MDM2 in malignant transformation of PA.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent survey, up to 50% of the patients had developed recurrences and up to 70% local or distant metastases (Gnepp et al, 2005). Very little is known about the genetic events leading to malignant transformation of PA (Rö ijer et al, 2002;DiPalma et al, 2005;Augello et al, 2006;Fowler et al, 2006;Ihrler et al, 2007) and there are no reliable molecular markers that can predict the risk of malignant transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Weber and co-workers analyzed TP53 mutations by direct sequencing of exons 4-9 and detected mutations in 4/42 PA and 3/12 myoepitheliomas [14]. Despite the evidence that TP53 might be altered in SGN [10,13,14,16,17,18], we sequenced all of our samples and found only four missense mutations, one nonsense TP53 mutation and a very low frequency of LOH at the 17p 13.1 region in our subset of salivary tumor samples.…”
Section: Discussionmentioning
confidence: 69%
“…Previous papers reported positive immunoexpression of p53 protein [8,9], yet TP53 mutations seem to be infrequent events in pleomorphic adenomas (PA), adenoid cystic carcinomas (ACC), mucoepidermoid carcinomas (MEC) and carcinomas ex pleomorphic adenomas (CAexPA) [10,11,12,13,14]. These previous papers relied on different techniques (SSCP, for example, which misses mutations when compared to direct sequencing), and in some of them, sequencing was only performed on a few samples.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that qMSP analysis could be developed as a useful clinical tool to differentiate between CPA and its benign precursor. Augello et al [13] reported that p16(INK4A) promoter hypermethylation was found in 100% (5/5) of carcinomas including 4 cases of cystic adenocarcinomas and 1 case of CPA. Patel et al [14] examined cyclin D1 and p16 expression in 43 parotid tumours (29 pleomorphic salivary adenoma and 14 carcinoma ex pleomorphic).…”
Section: Discussionmentioning
confidence: 99%